Exosome-mediated inhibition of microRNA-449a promotes the amplification of mouse retinal progenitor cells and enhances their transplantation in retinal degeneration mouse models - Chen Jun Guo; Xiu Li Cao; Yu Fei Zhang; Kang Yi Yue; Jing Han; Hong Yan; Hua Han; Min Hua Zheng (Elsevier, 2023)
Inherited and age-related retinal degenerations are the commonest causes of blindness without effective treatments. Retinal progenitor cells (RPCs), which have the multipotency to differentiate into various retinal cell types, are regarded as a promising source of cell transplantation therapy for retinal degenerative diseases. However, the self-limited expansion of RPCs causes difficulty in cell source supply and restrict its clinical treatment. In this work, we found that inhibition of microRNA-449a (miR-449a) in RPCs can promote proliferation and inhibit apoptosis of RPCs, partially through upregulating Notch signaling. Further optimization of transduction miR-449a inhibitor into RPCs by endothelial cell-derived exosomes can promote the survival of RPCs transplanted in vivo and reduce cell apoptosis in retinal degeneration mouse models. In summary, these studies have shown that exosome-miR-449a inhibitor can effectively promote the expansion of RPCs in vitro and enhance transplanted RPCs survival in vivo, which might provide a novel intervention strategy for retinal degenerations in the future.